Politeness Strategies: Negotiation in Procurement Services of Traditional Entertainments - Trihadmono, Eko Joko; Djatmika, Djatmika; Sumarlam, Sumarlam; Nurkamto, Joko (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
This paper aims to describe kinds of politeness strategies and features of the politeness in Javanese cultural context where Javanese people incur activities in the procurement of Javanese traditonal entertainments. The study used qualitative approach assigning 20 research subjects and analyzed 42 corpuses as the cources of data. Data of this study were divided into politeness techniques, politeness strategies, and impoliteness strategies. Results show that of five politeness strategies, one does not appear in the negotiation that is using affective tag to show a certain concern.Â Four techniques that appear are: to speak indirectly, to lie politely, to use euphimism, and to use modal tags to show uncertainty. Four politeness strategies, including bald on-record, positive politeness, negative politeness, and off-record politeness all exist as the medium of interactions. Finally, impoliteness strategies exist in the form of bald on-record impoliteness, negative impoliteness, positive impoliteness, and enternaining impoliteness.Â In context of Javanese culture, this study shows its novelty that Javanese culture has its own universal cultural values in politeness.